2022
DOI: 10.3390/biom12081033
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic Spatial Association between Ras and Phosphatidylserine on the Cell Membrane Studied with Multicolor Super Resolution Microscopy

Abstract: Recent work suggests that Ras small GTPases interact with the anionic lipid phosphatidylserine (PS) in an isoform-specific manner, with direct implications for their biological functions. Studies on PS-Ras associations in cells, however, have relied on immuno-EM imaging of membrane sheets. To study their spatial relationships in intact cells, we have combined the use of Lact-C2-GFP, a biosensor for PS, with multicolor super resolution imaging based on DNA-PAINT. At ~20 nm spatial resolution, the resulting supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…For instance, PS is the most abundant anionic phospholipid in mammalian cells [40]. Non-overlapping PS domains have been shown to exist in the cell PM [23,40,41]. PS has been shown to associate with the CHOL-independent KRAS4B nanoclusters in the PM (will be elaborated below, [23][24][25][26]42]).…”
Section: Phospholipids Laterally Segregate To Distinct Domains In Mem...mentioning
confidence: 99%
“…For instance, PS is the most abundant anionic phospholipid in mammalian cells [40]. Non-overlapping PS domains have been shown to exist in the cell PM [23,40,41]. PS has been shown to associate with the CHOL-independent KRAS4B nanoclusters in the PM (will be elaborated below, [23][24][25][26]42]).…”
Section: Phospholipids Laterally Segregate To Distinct Domains In Mem...mentioning
confidence: 99%
“…Furthermore, Ras (small GTPase) nanoclustering has been shown to be important in oncogenic signalling and attempts to disrupt Ras nanoclusters are being explored as a potential therapeutic strategy ( Van et al, 2021 ). Several studies have identified Ras interaction with phosphatidylserine in membrane clustering, and a recent super-resolution microscopy study defined the nanoscopic spatial membrane association between Ras and phosphatidylserine ( Koester et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Saturated fatty acids with 16 or more carbons are often connected to the sn-1 position in PS, whereas unsaturated fatty acids are typically located at the sn-2 position, even though the acyl chains in PS differ among cell types and organelles [19,20]. PS makes up a small portion of most cellular membranes [21,22]. The PS has an important role in the removal of apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%